Adaptation of international guidelines on assessment and management of cancer pain for the Australian context. Issue 2 (14th April 2015) - Lovell, Melanie; Luckett, Tim; Boyle, Frances; Stubbs, John; Phillips, Jane; Davidson, Patricia Mary; Olver, Ian; von Dincklage, Jutta; Agar, Meera
Abstract Aim To develop clinical practice guidelines for screening, assessing and managing cancer pain in Australian adults. Methods This three‐phase project utilized the ADAPTE approach to adapt international cancer pain guidelines for the Australian setting. A Working Party was established to define scope, screen guidelines for adaptation and develop recommendations to support better cancer pain control through screening, assessment, pharmacological and non‐pharmacological management, and patient education. Recommendations with limited evidence were referred to Expert Panels for advice before the draft guidelines were opened for public consultation via the Cancer Council Australia Cancer Guidelines Wiki platform in late 2012. All comments were reviewed by the Working Party and the guidelines were revised accordingly. Results Screening resulted in six international guidelines being included for adaptation – those developed by the Scottish Intercollegiate Guidelines Network (2008), National Health Service Quality Improvement Scotland (2009), National Comprehensive Cancer Network (2012), European Society of Medical Oncology (2011), European Association for Palliative Care (2011, 2012) and National Institute of Clinical Excellence (2012). Guideline adaptation resulted in 55 final recommendations. The guidelines were officially launched in November 2013. Conclusion International guidelines can be efficiently reconfigured for local contexts using the ADAPTE approach. Availability of the guidelines via the Cancer Council Australia Wiki is intended to promote uptake and enable recommendations to be kept up to date. Resources to support implementation will also be made available via the Wiki if found to be effective by a randomized controlled trial commencing in 2015.